Neurath, Passeron, and protocol sentences in sociology - Moreno-Pestaña , José Luis; Costa-Delgado , Jorge (Cinta de Moebio. Revista de Epistemología de Ciencias Sociales, 2022)
The central aim of this paper is to explain how protocol sentences establish a specific space for scientific discussion at the level of observation in the social sciences. In this space, the four levels of the theory of protocol sentences work as a coordinate system that allows to specify the degree of quality of data production. To do so, we elaborate upon Jean-Claude Passeron’s epistemology by combining it with Otto Neurath’s theory of protocol sentences. We start by discussing Passeron’s interpretation of Neurath’s work in Le raissonnement sociologique and then present Neurath’s theory, following Thomas Uebel’s interpretation, with the purpose of developing the potential of Passeron’s epistemology in this regard.